PERSEPSI MASYARAKAT TENTANG PERNIKAHAN DINI DI KECAMATAN KOTO TANGAH KOTA PADANG - Nita Tri Putri; Nurdin Nurdin; Padila Rizkia Fajariani (Maternal Child Health Care, 2021)
Analysis of child marriage data in Indonesia records that more than 700 million women living today are married before reaching adulthood, the age of 18 years. Based on KUA data from Padang in the last 3 years, Koto Tangah District there was an increasing of teenagers who marry early. In 2017, there werefrom 67 to 423 young women getting early marriages in Koto Tangah Sub district from 1472 young women marriages in Padang. The type of study was qualitative with phenomenological approach. The data were collected through in-depth interviews. The selection of information used purposive sampling technique. There were 11 informants were chosen. They were 6 early couples married, 3 parents, 1 health worker and 1 officer in BKKBN office Padang. It was conducted on January-May 2019. The results of this study showed that the public perception of early marriage can be seen from internal factor (self-desire) and external factors (economy, low education, parents' concerns, promiscuity and pregnancy outside marriage). For some people, early marriage was considered as a normal. Then, the health workers had attempted to reduce the number of early marriages by holding youth integrated services post and BKKBN office staff with Generasi Berencana program for both schools and non-schools.